Analysis of aesthetic values in works of art–Taking the Picture of the Displaced People as an Example - Wang, XinJing (International Theory and Practice in Humanities and Social Sciences, 2025)
The cultural program "Partial" cuts into the field of art with a unique perspective. Each episode is centered on a specific theme, and through telling the historical and cultural stories of different countries, it incorporates Chen Danqing’s profound understanding and unique insights into art. The program directs viewers’ attention to the beauty of details that are often overlooked, thus stimulating viewers’ thinking and emotional resonance. This paper takes the interpretation of "The Picture of the Displaced People" in the first season of "Partial" as an example, combines the contemporary social background, uses the theory of art aesthetics, and deeply analyzes the embodiment of the aesthetic value level in the art works. Through the analysis of this classic case, it explores how the program, while disseminating artistic knowledge, triggers the audience to think deeply about the relationship between art and society, history and reality, and provides new perspectives and thinking paths for the study of the aesthetic value of art works.